تركیا و مشروع الشرق الأوسطي (Journal of the College of Education for Women, 2019)
Turkey came back to the Middle East hardly after long disappearancethroughout its moderate regional policy, which put its in the middle of theevents it reverse its place throughout the regional references in the region,the way of coming back was too difficult and hard, the internal Turkishtroubles and inhibitors coming together with the maintenance bonds thatforms great complex barrier.But the great Turkish foreign policy represented by the foreign ministerAhmed David Oghlu, can successfully pass these problems and as a result itwithdraw turkey both geographical and political to its neighbor after longperiod of disappear, it new regional policies cancel the old impressions thatwas still in the mind of the other, especially the old impression that said thateither going east or west, this is the old idea in the past that said if you wantto go to Europe or west this will delay the bonds or bridge formation with theeast. But now Turkish policy leaves the old policies by educational andintellectual way based on political imagination and ambitious thinking doesn’tknow the impossible.It relay all of that on actual bases reflect deep consciousness in thecomposition of the region, it achieve its valuable position throughout itsregional balance and policies. It seems from the first impression there iscertain interaction on its aim for making relationship between the middle eastand European union, it’s in correct impression for many reasons, one frommost important reason because of the new Turkish policies that make itacceptable from many countries from the world and among the world sothroughout the Turkish role in the middle east it give insurance to the Europethat it may play the same role in the solving of the middle east troubles thiswill keep the advantage of the Europe within the region. This will lead thatturkey play a central role between the Middle East and Europe, but thereduction of the Turkish foreign policy by choosing between either west oreast policy this will make turkey go back to the old historical era, that make itlose its new varieties and sedation.Turkish new policy achieve many success not only just in the securitybut it achieve new ideological content in contrast to some of the radicals inthe past era who refuse the Islamic ottoman history, the justice anddevelopment party take its idea and policy from Islamic history of turkey. Inspite of that Ankara don’t leave the idea for joining the European Union. Inaddition to that turkey on of the most developed country in the middle east ithas affective and modern democratic regime in the region, and productive economy and it discover new balance between the religion and secular sothat the security aspect of the middle east will accept and support turkey, itsupport its goal in control as a big country developed both industrially andcivilization ally.